Color and number preferences of patients with psychiatric disorders in eastern Turkey - Kuloglu, M; Atmaca, M; Tezcan, AE; Unal, A; Gecici, O (Sage Publications Inc, 2002)
Color and number preferences have not been studied in healthy subjects and psychiatric patients in Turkey. The study group consisted of a total of 500 patients who had been referred to Firat University Medical Faculty Psychiatry Clinic between March and July 2000 and diagnosed a psychiatric disorder according to DSM-IV criteria. Preferred colors were requested as a selection from the Luscher Color Test. Then the patients were told to choose a number between 0 and 9. Green was the most frequently preferred of all colors and the number 3 was the most preferred number. Our results demonstrate that patients' choice of color and number reflect the region's religious and cultural milieu.
Keywords: Blue